Meningkatkan Keterampilan Berbicara Siswa dengan Menggunakan YouTube untuk Pembelajaran Bahasa Inggris Maritim di Akademi Maritim Nusantara - Yoana Gita Pradnya Lengari (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2022)
One of the tools that can help teachers and students in a classroom’s teaching and learning program is media. Visual and audio are two kinds of media that can be used as tools to facilitate activities in class, especially in language teaching and learning. One of the most common media to be used worldwide is YouTube. Not only that it is an entertaining media source, but also YouTube can play a great deal in aiding students’ learning process. The aims of this study are describing how YouTube videos can be used to enhance the students’ speaking skill, and describing the process of utilizing YouTube videos in language teaching-learning activity. The subject of this study is the students of the third semester in the Marine Engineering Program at Akademi Maritim Nusantara. The classroom action research design is used as the method to conduct this study. Data collections are obtained by speaking interview and assessment. The result of the study which was conducted in two cycles showed that, the average score of speaking indicators of the students increased from 60.8 to 66.3 in Cycle One. In Cycle Two, the improvement was progressing to 76.4 on the average score of speaking indicators. From those results, the study concluded that there was an improvement in the students’ speaking skill. The students’ fluency, pronunciation, vocabulary, context, and grammar can be seen as the improving aspects of the students’ speaking skill. In conclusion, the use of YouTube videos to improve students’ speaking skill is reviewed.